Variáveis Macroeconômicas e sua relação com Indicadores Econômicos, Financeiros e Sociais: um estudo de empresas brasileiras de construção civil listadas na B3 - Leonardo de Lima Neves (2021)
This study aimed to identify the relationship between variables related to the country's economic context, with the behavior of economic, financial, and social indicators of Brazilian construction companies, between 2010 and 2019. Thus, the economic context was represented by four macroeconomic variables, namely: (i) GDP variation, (ii) inflation rate, (iii) exchange rate and (iv) interest rate. Through a systematic review and previous studies that addressed the topic, seven indicators were selected, namely: (i) spending on personnel (GP), (ii) spending on taxes (GT), (iii) spending on remuneration third-party capital (GRCT), (iv) expenditure on remuneration of equity capital (GRCP), (v) Return on investment (ROI), (vi) Ebitda Margin (MrgEBIT) and (vii) Current Liquidity (LC). Considering the General Theory of Systems and Theory of Business Cycles, this research has as a guiding hypothesis that there is a relationship between the macroeconomic variables and the indicators of civil construction companies listed in B3. Descriptive methodology was used regarding the objective; document to procedures; and quantitatively, in terms of approaching the problem. Therefore, the panel data econometric model was used to capture the relationship between the variables. Regarding the findings of this study, it is noted that in the period analyzed, the variation in GDP and the interest rate did not show any statistically significant relationship with one of the seven indicators of an economic, financial, and social nature. The exchange rate, on the other hand, had a statistically significant negative relationship with the indicator of a social nature, the GP. The same happens between the inflation rate and the GRCP. Furthermore, the inflation rate showed a statistically significant positive relationship with the GP. Thus, the study results contribute to the field of scientific research by verifying and confirming that the external environment, represented by the landmark scenario, exerts influence within organizations in the Brazilian civil construction industry.